2014
DOI: 10.1371/journal.pone.0085939
|View full text |Cite
|
Sign up to set email alerts
|

Adipokines and Obesity Are Associated with Colorectal Polyps in Adult Males: A Cross-Sectional Study

Abstract: BackgroundObesity increases the risk of colon cancer. It is also known that most colorectal cancers develop from adenomatous polyps. However, the effects of obesity and adipokines on colonic polyp formation are unknown.MethodsTo determine if BMI, waist circumference or adipokines are associated with colon polyps in males, 126 asymptomatic men (48–65 yr) were recruited at time of colonoscopy, and anthropometric measures as well as blood were collected. Odds ratios were determined using polytomous logistic regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 67 publications
7
50
0
1
Order By: Relevance
“…As previously published (11), 57 (45%) of the 126 participants had at least one polyp, and 23 (18%) had ≥ 3 polyps. 37 (29.4%) of the participants had a tubular adenoma.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…As previously published (11), 57 (45%) of the 126 participants had at least one polyp, and 23 (18%) had ≥ 3 polyps. 37 (29.4%) of the participants had a tubular adenoma.…”
Section: Resultssupporting
confidence: 75%
“…At the time of enrollment, immediately prior to routine colonoscopy, written informed consent was obtained and clinical metadata on subject co-morbidities, current medications, and family history were collected. Anthropometric measures were taken to calculate BMI and to record waist circumference (11). Also at the time of enrollment, venous blood was drawn, and serum was isolated by standard procedures and stored at −80°C.…”
Section: Methodsmentioning
confidence: 99%
“…Healthy males (n=126, > 96% Caucasian) ranging from 48–65 years of age were screened and recruited as previously reported [15]. Participants were weighed and measured by trained staff.…”
Section: Methodsmentioning
confidence: 99%
“…Subjects with metabolic syndrome, which includes obesity, diabetes, and pulmonary disease, are at a higher risk for advanced neoplasms found during colonoscopy [30]. In a case-control study of 126 asymptomatic men recruited at colonoscopy, the risk of adenoma directly correlated with BMI and elevated circulating adipokines, suggesting that these obesity-related hormones may influence the development of polyps [31]. In addition to the abundance of clinical data correlating obesity and CRC, there is genetic data linking the two diseases; an international study evaluating the correlation of genetic polymorphisms in obesity-related genes with the incidence of CRC found that two genes had polymorphisms significantly associated with risk of CRC [32].…”
Section: Inflammatory Bowel Disease (Ibd) Either Ulcerative Colitis Ormentioning
confidence: 99%